Implementasi Metode UCD Dalam Perancangan Sistem Pakan Ayam Otomatis - Muhammad Ferdian Pradana; Evi Dwi Wahyuni; Zamah Sari (Jurnal Repositor, 2025)
This research designs an automatic chicken feeding system by applying the User-Centered Design (UCD) method to increase efficiency and effectiveness in the feeding process. The research process began with problem identification through observations and interviews with chicken farmers, who revealed difficulties in managing feed and monitoring cage temperature. Next, a literature study was carried out to explore related theories, followed by prototype design which included wireframes and prototypes. The resulting prototype was tested using the Cognitive Walkthrough (CW) method, showing a successful task completion rate of 100% and an average completion time of 11.91 seconds. To evaluate user satisfaction, testing was carried out using the Single Ease Question (SEQ) method, which resulted in an average score of 6.44 out of 7. These results indicate that the designed system is not only easy to use, but also meets user needs in feed management. This research contributes significantly to the development of technological solutions for more efficient chicken farming.